Serotonin receptor diversity in the human colon: Expression of serotonin type 3 receptor subunits 5-HT3C, 5-HT3D, and 5-HT3E - Kapeller, Johannes (2011)
Since the first description of 5-HT(3) receptors more than 50 years ago, there has been speculation about the molecular basis of their receptor heterogeneity. We have cloned the genes encoding novel 5-HT3 subunits 5-HT3C, 5-HT3D, and 5-HT3E and have shown that these subunits are able to form functional heteromeric receptors when coexpressed with the 5-HT3A subunit. However, whether these subunits are actually expressed in human tissue remained to be confirmed. In the current study, we performed immunocytochemistry to locate the 5-HT3A as well as the 5-HT3C, 5-HT3D, and 5-HT3E subunits within the human colon. Western blot analysis was used to confirm subunit expression, and RT-PCR was employed to detect transcripts encoding 5-HT(3) receptor subunits in microdissected tissue samples. This investigation revealed, for the first time, that 5-HT3C, 5-HT3D, and 5-HT3E subunits are coexpressed with 5-HT3A in cell bodies of myenteric neurons. Furthermore, 5-HT3A and 5-HT3D were found to be expressed in submucosal plexus of the human large intestine. These data provide a strong basis for future studies of the roles that specific 5-HT(3) receptor subtypes play in the function of the enteric and central nervous systems and the contribution that specific 5-HT(3) receptors make to the pathophysiology of gastrointestinal disorders such as irritable bowel syndrome and dyspepsia.